2021
DOI: 10.1108/pr-11-2018-0465
|View full text |Cite
|
Sign up to set email alerts
|

The influences of abusive supervision on job satisfaction and mental health: the path through emotional labor

Abstract: PurposeThe purpose of the study is to empirically test and explore the influences of abusive supervision on subordinates' job satisfaction and mental health. Specifically, the authors focus on the mediation effects of emotional labor and compare the discrepancies between surface acting and deep acting.Design/methodology/approachTime-lagged data were obtained from 239 employees in the hospitality industry in Taiwan. The hypothesized model was tested using structural equation modeling with Mplus 7.4.FindingsResu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 83 publications
(129 reference statements)
1
13
0
Order By: Relevance
“…The topic of promoting healthy workplaces and empowering employees to mirror recent research trends toward examining the relationships between positive psychological states and organizational well-being (Maslach et al , 2001; Van Den Bergh, 2000). Similarly, the results of our study echo past empirical studies that found negative relationships between abusive supervision employees’ mental health and psychological well-being in hospitality employees (Nyberg et al , 2011; Wang et al , 2021).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The topic of promoting healthy workplaces and empowering employees to mirror recent research trends toward examining the relationships between positive psychological states and organizational well-being (Maslach et al , 2001; Van Den Bergh, 2000). Similarly, the results of our study echo past empirical studies that found negative relationships between abusive supervision employees’ mental health and psychological well-being in hospitality employees (Nyberg et al , 2011; Wang et al , 2021).…”
Section: Discussionsupporting
confidence: 89%
“…We adopted our scale from the 12-item General Health Questionnaire (GHQ-12) developed by Goldberg and Williams (1988). Although GHQ is widely used as an indicator of stress and has been widely applied in the service industry and has been verified in different language and cultural contexts (Murray-Gibbons and Gibbons, 2007; Shevlin and Adamson, 2005; Ye, 2009), the factor structure of the scale remains inconclusive (Andrich and Van Schoubroeck, 1989; Daradkeh et al , 2001; Hankins, 2008; Politi et al , 1994; Sánchez-López and Dresch, 2008; Schmitz et al , 1999; Wang et al , 2021). We used four items to assess employees’ general mental health, including items such as “Could not overcome difficulties,” “Feeling unhappy and depressed,” “Losing confidence,” and “Thinking of self as worthless.” All four items were reverse scaled.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface acting includes the display of emotions that are not actually felt by the careful use of verbal and non-verbal communication tools such as facial expressions, gestures, and tone of voice [7,11,53]. The contradiction of the real feelings that individuals feel with the emotional displays expected by the organization can be expressed as surface acting.…”
Section: Emotional Labormentioning
confidence: 99%